ASSOCIATION OF HYPERTENSION IN PREGNANCY WITH THE INCIDENCE OF LOW BIRTH WEIGHT - Primasari, Nina (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2024)
The incidence of birth with low birth weight babies (BBLR) is one indicator that contributes to high perinatal morbidity and mortality rates and is at risk of experiencing obstacles in growth and development. BBLR accounts for 60% to 80% of neonatal deaths with the global prevalence of low birth weight is 20 million per year or 15.5% of all babies born in the world (WHO, 2015). Hypertension in Pregnancy (HDK) is one of the factors that can affect the occurrence of low birth weight (Julia, et al.2016). Hypertension in Pregnancy is a medical condition of pregnant women with non-normotensive blood pressure, reaching >140/90 mmHg at systolic pressure and diastolic pressure, which causes a decrease in uteroplacental perfusion or decreased blood circulation to the fetus as a result of which the fetus lacks oxygen and nutrients. This can cause stunted fetal growth and manifestation of BBLR. The purpose of the study was to determine the relationship between hypertension in pregnancy (HDK) with the incidence of low birth weight (BBLR). This study used a cross-sectional design. Data collection was carried out retrospectively using medical record/resume data. The sample used was 181 respondents. Data analysis using chi square test.